NOISE EFFECTS USING TRANSITION METAL CATALYTIC CONVERTER CHROME-COATED COPPER ON FOUR STROKE MOTORCYCLES - Sudirman Rizki Ariyanto; Wahyu Robby Cahyadi; Bagas Surya Hadi; Warju Warju; Muhammad Yandi Pratama (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2022)
Over the past few years, the Transition Metal Catalytic Converter (TMCC) has become a standard of the exhaust system of internal combustion engines. Besides being used to reduce exhaust emissions, TMCC also has a certain effect on the noise produced. In this study, the effect of noise in the use of TMCC chrome plated copper (CuCr) was investigated. The noise test was carried out in two conditions with the same vehicle, by using a 2005 Honda Supra Fit with standard exhaust conditions and using TMCC CuCr. Noise testing was carried out based on the ISO/FDIS 5130 standard, and then the results were compared with the noise standard regulated in Permen LH No. 7 of 2009. The findings show that the use of TMCC CuCr is less efficient in reducing the vehicle noise. This is proven from the comparison results which show that on average the TMCC CuCr exhaust tends to be 10% louder than the standard exhaust. The noise test results show that the measured noise at RPM 5000 is 82.2 dBA for standard exhaust and 95.4 dBA for TMCC CuCr exhaust, while the noise standard stipulated in Ministerial Regulation No. 7 of 2009 is only 90 dBA. Through these results, it can be concluded that the use of TMCC CuCr exhaust does not accordance with the government standards and included in